Evaluation of Urban Heat Island (UHI) Spatial Change in Freshwater Lakes with Hot Spot Analysis (GI Statistics) - Gunathilaka, M. D. K. L.; Harshana, W. T. S. (Three E Science Institute, 2021)
Monitoring spatial changes of surface heat island formation and temperature changes in sub-urban areas is vital in the freshwater lake management of urban areas as frequent phenomena related to climate change have undergone. The purpose of this study was to examine the Spatio-temporal pattern of urban heat island and land surface temperature and vegetation changes by using GI statistics, where hotspot analysis was also performed. The study further examined the effect of heat island and surface temperature on urban freshwater lakes where hot and cold spots identified had undergone a reclassification process. The results revealed that the increasing Land Surface Temperature (LST) due to modification and transformation of vegetated areas into concrete and synthetic built-up extents is one of the challenging problems in the selected suburbs. Both NDVI and LST hot spots and cold spots have changed compared to 2010. The LST showed considerable expansion of the hotspots within ten years rather than cold spots in all three suburbs. The freshwater lakes are in proximity to the city. All three lakes were finally reclassified as hotspot areas for LST, while Kesbewa Lake and Thalangama Lake were identified as NDVI hotspots where the vegetation cover had contracted by 2020. Even though Boralesgamuwa Lake is not recognized as an NDVI hotspot, the encroachment and expansion of the current hotspot area could be identified. The study's findings could be used to design sustainable cities in these suburbs more by prioritizing the conservation of urban ecosystems.